Entrepreneurship in times of economic stress: unraveling the U-shaped relationship between the internality of causal attributions and growth - GUILHERME FOWLER DE AVILA MONTEIRO (2024)
Purpose – This paper examines the relationship between entrepreneurs’ internality of causal attributions and firm growth during an economic crisis. We propose a U-shaped relationship between the two variables, arguing that the highest-growth entrepreneurs are those with either the highest or lowest levels of internal attribution (IA) during such periods.